2008
DOI: 10.1029/2007ja012468
|View full text |Cite
|
Sign up to set email alerts
|

Energization of radiation belt electrons by ring current ion driven ULF waves

Abstract: [1] In this paper we examine the hypothesis that MeV energy radiation belt electrons can be energized by ULF waves, the ULF waves themselves being excited by drift-bounce resonance with energetic ring current ions. We show that this energization is most likely to occur during depleted plasmatrough conditions and when the plasmapause lies on a low L-shell. For example, when the plasmasphere has been eroded so that the plasmapause lies at L = 3, then efficient energization for electrons with energies >1 MeV at L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 49 publications
5
59
0
Order By: Relevance
“…Other MLT sectors (analysed in this study but not shown here) demonstrate similar dependencies on solar wind variability. We only show the dependence of radial (B x ) magnetic component corresponding to the poloidal Alfvén waves expected to be the most relevant to drift resonance interactions with radiation belt electrons (Ozeke and Mann, 2008). The other two magnetic components (azimuthal B y and compressional B z ) demonstrate similar solar wind dependencies supporting the conclusions below.…”
Section: Solar Wind Datasupporting
confidence: 50%
“…Other MLT sectors (analysed in this study but not shown here) demonstrate similar dependencies on solar wind variability. We only show the dependence of radial (B x ) magnetic component corresponding to the poloidal Alfvén waves expected to be the most relevant to drift resonance interactions with radiation belt electrons (Ozeke and Mann, 2008). The other two magnetic components (azimuthal B y and compressional B z ) demonstrate similar solar wind dependencies supporting the conclusions below.…”
Section: Solar Wind Datasupporting
confidence: 50%
“…For example, Ozeke and Mann [2001] modeled the drift bounce instability in the magnetosphere and found that high-m number waves can be driven by ring current ions. These high-m number waves in turn become potential accelerators for radiation belt electrons through drift resonance [Ozeke and Mann, 2008]. The ST-5 observations reveal that these waves have a very high occurrence rate in the dayside magnetosphere (Figure 4) even though the observations are made mostly during quiet and moderately active geomagnetic conditions.…”
Section: High-m Number Ulf Wavesmentioning
confidence: 99%
“…Because of the known energy dependence of ω d and ω b , the resonance energy can be determined in theory if the wave properties are known. For the case of electrons, it should be noted that the bounce frequency is usually much higher than the other two frequencies [27,59]. Figure 6 gives a schematic view of the behavior of resonant particles in the poloidal standing waves with different harmonics.…”
Section: Fast Acceleration Of Ions By Poloidal Ulf Wavesmentioning
confidence: 99%